The Role of Consumer Satisfaction as a Mediating Factor in Mediating the Influence of Usability on the Intention of Reuse of the Shopeefood Application in the City of Denpasar - Ridho, Ahmad; Kusumadewi, Ni Made Wulandari (Formosa Journal of Applied Sciences, 2024)
Shopee Food is one of the providers of food delivery services but currently holds the second position when compared to its competitor. This is attributed to the limited interest of consumers in reusing the application, influenced by the ease with which a consumer can use the application. This study aims to analyze the factors of consumer satisfaction in mediating the influence of usability on reuse intention of ShopeeFood application in Denpasar City. The study was conducted in Denpasar city with a sample size of 120 respondents, The findings of this research include: 1) ease of use significantly and positively influences reuse intention, 2) ease of use significantly and positively influences consumer satisfaction, 3) consumer satisfaction significantly and positively influences the reuse intention, and 4) consumer satisfaction acts as a mediating variable in the influence of usability on the reuse intention.